OPTIMALISASI TEKNOLOGI UNTUK MENINGKATKAN INOVASI PEMBELAJARAN SENI RUPA KELAS IV DI SD NEGERI BALARAJA I - Rakhman, Patra Aghtiar; Rokmanah, Siti; Najib, Muhamad Ainun (Indonesian Journal of Elementary Education (IJOEE), 2023)
Fine art learning in elementary schools is taught by classroom teachers whose educational background is not necessarily art either. This will certainly have an impact on the learning activities carried out. The lack of learning innovation will eventually have implications for the low creativity of students. Therefore, increasing teacher competence and developing learning innovations needs to be done, one of which is by optimizing current technology. Technology is present to facilitate various human jobs. Through this research, some activities and efforts that can be done to increase the innovation of fine arts learning with the help of technology will be described. Qualitative research method with descriptive data display is the method used in this research, with three important stages, namely data collection through interviews, observations, and document studies, data reduction to conclusion drawing, and data validity testing with triangulation techniques. Innovation in fine arts learning in class IV SD Negeri Balaraja I is carried out by increasing teacher competence in fine arts learning, and developing fine arts learning activities by optimizing the use of technology in learning, Technology is also used to establish cooperation and collaboration with parents and partners. It aims to create innovative fine art learning and the ability of students to create original and varied works of art.